If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 3(c + -9) Reorder the terms: 21 = 3(-9 + c) 21 = (-9 * 3 + c * 3) 21 = (-27 + 3c) Solving 21 = -27 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 21 + -3c = -27 + 3c + -3c Combine like terms: 3c + -3c = 0 21 + -3c = -27 + 0 21 + -3c = -27 Add '-21' to each side of the equation. 21 + -21 + -3c = -27 + -21 Combine like terms: 21 + -21 = 0 0 + -3c = -27 + -21 -3c = -27 + -21 Combine like terms: -27 + -21 = -48 -3c = -48 Divide each side by '-3'. c = 16 Simplifying c = 16
| 6x-2(-6+3)=120 | | 3a+3b+3c=3b | | 7x-2-3x=-10 | | x+3.6=0.5 | | 2(8+4*2)= | | Y=(2t^2)+1 | | 5x+7(4x+7)=-149 | | -6(2x-7)=-12x+42 | | 6-5x=-39 | | 27x^3+9x^2+3x-3=0 | | 0.83x=35 | | 30+8=74 | | 5(k-5)-4(k+1)-13=-33 | | x=x^2-4x+2 | | Y=2t+1 | | .5x-7=0.1(x+10) | | -6(2w+1)-w=33 | | .5x-7=.1(x+10) | | 7x-11=16-2x | | -6x-3x-15=-9-2x | | 8=-4(c+6) | | 2x+(2y-164)=992 | | 36-3(2w+1)=9w-3(w+2) | | 15-7x=1-5x | | 16x+8y=-28 | | 5(2*3-3)= | | 5h=-60 | | -7x+10+8x=5+x+5 | | 2y-9=8y+21 | | y-6y=9+6 | | 7x+1x-9=2(4x+9) | | 15x-6=35x+2 |